O genezie instytucji usiłowania i pracach nad jej ujęciem w projekcie polskiego kodeksu karnego z 1932 roku - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper presents the origins of attempt as well as the work conducted in the Criminal Unit and the Criminal Law Section of the Codification Commission of the Republic of Poland on the juridical construction of attempt. The discussion and analysis are based on the papers delivered during a meeting of the section by Juliusz Makarewicz and Aleksander Mogilnicki. The proposals presented in them were used in the final version of Chapter III of the draft Polish Criminal Code. The author demonstrates that the construction of attempt was shaped by in-depth discussions within the criminal law section. The aim was to codify attempt in a modern manner in the Criminal Code, taking into account earlier legislation as well as legal doctrine.
Keywords: Codification Commission; Makarewicz, Juliusz (1872-1955); Mogilnicki, Aleksander; draft Criminal Code